Synthesis and Characterization of New Compounds Derived from Pyrrolidine-2-One and Evaluation of their Biological Activities - A. Betti, Nadia; Ib. Hussain, Redha; Ab. Kadhem, Sahar; Jabar Kh. Atia, Abdul (Al-Nahrain Journal of Science, 2020)
New derivatives of pyrrolidine-2-one have been prepared by lactamization of g-butyrolactone GBL with hydrazine hydrate (NH2NH2 (80%)) to afford (1-aminopyrrolidin-2-one) which undergo many reactions to prepare the other derivatives. The prepared derivatives were determined by utilizing their FT-IR, 1H-NMR and some by Mass spectrum. These derivatives were evaluated biologically against (Staphylococcus aureus and E. coli). Some of these derivatives exhibited good biological activity against one or both kind of bacteria while some exhibited no biological activity at all.